Policy Influence of Family Hope Program to Reduce the Poverty in Takalar, Indonesia - Nuryanti Mustari; Lukman Hakim; Erni Erni; Maharanny Puspaningrum (Department of Government Studies Universitas Muhammadiyah Makassar, 2019)
This article analyze about policy influence of Family Hope Program toward reduce the poverty in Bontolebang Village, North Galesong Subdistrict. The methodology of this research is mix methods that combine quantitative and qualitative approach with questionnaire and interview instrument. The determination of sample in this research uses probability sampling techniques, the category of sample is beneficiary participant of the Family Hope Program but because the spectrum of population is too large so it just takes 80 people and 3 informants. Data collection technique are observation, questionnaire, interview, and documentation. Data analysis technique use regression analysis. Data validity technique are validity and reability testing. The result of this research indicate that policy influence of Family Hope Program in Bontolebang Village, North Galesong Subdistrict went very well. This is based on the average score obtained from statement item amounts 266,9 or 83,41% which indicate that implementation of Family Hope Program occupies on the very good category. Afterwards, this research indicate that policy of Family Hope Program has positive and significant effect on poverty reduction amounts 62,7% and the rest amounts 37,3% caused by other programs from the government.